2019
DOI: 10.15244/pjoes/96259
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Different Indicators to Evaluate Chernozems Fluvisols Physical Quality in the Odra River Valley: A Case Study

Abstract: Soil quality is a very important issue that continuously evaluates and develops in different countries. The concept of soil quality was developed in the 20 th century and contains three main aspects: physical, chemical and biological [1][2][3]. From an agricultural point of view, soil physical quality (SPQ) decreases mainly in cases of soil cultivation due to decreases in soil porosity, increased soil bulk density (BD), aeration and water balance, as well as increases in soil penetration resistance, structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…is is inferred from what was found in regions with similar texture in "Maria da Conceição," probably due to the presence of native vegetation. Studying Haplic Cambisols, Oliveira et al [27] found that preserved forest areas presented the best water retention conditions, which is significantly correlated with S [35], thus endorsing the conjecture in the present work. Moreover, as illustrated in Dexter [11], the S index is mostly determined by soil organic carbon, being positively correlated [36], since organic carbon can increase water retention and improve pore distribution [37].…”
Section: Resultssupporting
confidence: 88%
“…is is inferred from what was found in regions with similar texture in "Maria da Conceição," probably due to the presence of native vegetation. Studying Haplic Cambisols, Oliveira et al [27] found that preserved forest areas presented the best water retention conditions, which is significantly correlated with S [35], thus endorsing the conjecture in the present work. Moreover, as illustrated in Dexter [11], the S index is mostly determined by soil organic carbon, being positively correlated [36], since organic carbon can increase water retention and improve pore distribution [37].…”
Section: Resultssupporting
confidence: 88%
“…The silt loam is the predominant soil texture. The SD values (Tables 3 and 4) for most soil properties are large, indicating moderate to strong variability; this is not uncommon for soils [12,57,58]. Typically, the CV values are < 45%, indicating the mean variability of the measurement data.…”
Section: Resultsmentioning
confidence: 94%
“…A BD''between 1.3 and 1.55 g cm and greater than 1.8 g cm −3 is considered extremely bad'' (Mukhopadhyay et al, 2019). The BD values greater than 1.25 1.30 g•cm -3 could cause yield loss due to poor soil aeration (Borek, 2019). In the investigated soils due to the clayey high values , the root growth could be and consequently the plant cm −3 is fair, is considered extremely bad'' (Mukhopadhyay et al,…”
Section: Resultsmentioning
confidence: 99%